KARAKTERISTIK BRIKET DARI SEKAM PADI DAN KETAMAN KAYU BERPEREKAT DAUN JAMBU METE (Talenta Publisher (Universitas Sumatera Utara), 2016)
Briquettes are biomass compaction technology as alternative energy sources with or without binder in different shape and size. The research is aimed to analyze the best carbonization process, compaction pressure and binder concentration for quality of briquettes. In this resarch, rice husk and wood shaving are used as raw materials carbonized at different process, named by carbonization process 1 and other carbonization process 2. Carbonization process 1 was done by carbonized each raw material and then mixed while carbonization process 2 was done by mixed raw materials then carbonized. Raw materials were blended with cashew nut leaves binder at concentration 10%, 12,5%, 15%, and 20% and then compacted at pressure 85 kg/cm2 and 105 kg/cm2. The best briquette was briquette that rice husk and wood shaving were carbonized by carbonization process 1 blended with 15% binder and compacted at 85 kg/cm2 and had calorific value 2045,8271 cal/g.